1996
DOI: 10.1155/s0161171298000660
|View full text |Cite
|
Sign up to set email alerts
|

Commutativity results for semiprime rings with derivations

Abstract: ABSTRACT. We extend a result of Herstein co,cerning a derivation d on a prime ring R satisfying [d(x),d(y)] 0 for all x,y R, to the case of semiprime rings. An extension of this result is proved for a two-sided ideal but is shown to be not true for a one-sided ideal. Some of our recent results dealing with U*-and U**-derivations on a prime ring are extended to semiprime rings. Finally, we obtain a result on semiprime rings for which d(xy) d(yx) for all x,y in some ideal U.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…This result was extended for semiprime rings in [8] by Daif. Further, for semiprime rings, Andima and Pajoohesh [3] showed that an inner derivation satisfying the above mentioned condition on a nonzero ideal of must be zero on that ideal.…”
Section: Introductionmentioning
confidence: 78%
“…This result was extended for semiprime rings in [8] by Daif. Further, for semiprime rings, Andima and Pajoohesh [3] showed that an inner derivation satisfying the above mentioned condition on a nonzero ideal of must be zero on that ideal.…”
Section: Introductionmentioning
confidence: 78%
“…In [10] Herstein proved that if a prime ring R of characteristic different from two admits a nonzero derivation d such that [d(x), d(y)] = 0 holds for all x, y ∈ R, then R is commutative. Daif in [8] extended this result for semiprime rings.…”
Section: Lemma 1 ([1] Lemma 1) Let R Be a Ring P Be A Prime Ideal Omentioning
confidence: 75%
“…In [13], Herstein proved that if R is a prime ring of characteristic not two admitting a nonzero derivation d such that [d(x), d(y)] = 0 for all x, y ∈ R, then R is commutative. Further, Daif [10] showed that a 2-torsion free semiprime ring R admits a nonzero derivation d such that [d(x), d(y)] = 0 for all x, y ∈ I, where I is a nonzero ideal of R, then R contains a nonzero central ideal. In [15], Lanski prove that if L is a noncommutative Lie ideal of a 2-torsion free prime ring R and d, h are nonzero derivations of R such that [d(x), h(x)] ∈ C for all x ∈ L, then h = λd, where λ ∈ C. Very recently, the first author together with Dar [11] proved the following result: Let R be a prime ring with involution * of the second kind such that char(R) = 2.…”
Section: Introductionmentioning
confidence: 99%